Clinicians prescribe antibiotics for childhood respiratory tract infection based on assessment, rather than parental expectation. (10th January 2020) - Cook, Rob; Davidson, Peter; White, Alicia
The study: Cabral C, Horwood J, Symonds J, et al. Understanding the influence of parent-clinician communication on antibiotic prescribing for children with respiratory tract infections in primary care: a qualitative observational study using a conversation analysis approach. BMC Fam Pract 2019;20:102. This project was funded by the NIHR School for Primary Care Research Programme (project number SPCR204). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000829/gps-assessment-not-parental-expectation-drives-antibiotic-prescribing